Deviations from equal temperament in tuning isolated musical intervals - RAKOWSKI, Andrzej; MIŚKIEWICZ, Andrzej (Archives of Acoustics, 1985)
Four music students tuned the frequency of a variable-tone oscillator to set it at given musical intervals up and down from the reference tone of 500 Hz. Pure tones and complex tones were used. Despite the dispersion of the results a general tendency appeared: small intervals were mostly diminished and large intervals mostly enlarged in comparison with their equally-tempered values. No distinct dependence of the size of musical intervals on the sound spectrum could be observed.